Enhancing Eye–Hand Coordination in Early Childhood through Sensorimotor Play with Clamp Media: A Classroom Action Research - Rini Kurniawati; Moh Safik Almubarok; Nadiah Ismaeil (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Eye–hand coordination is a fundamental component of fine motor development, underpinning essential skills such as writing and cutting, and therefore needs to be optimally stimulated from an early age. However, many early childhood learners still demonstrate limited visual–motor integration, indicating the need for effective and engaging learning strategies. This study aims to improve the eye–hand coordination of children aged 4–5 years through the application of a sensorimotor play method using clamp media. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles. The participants consisted of 18 children enrolled in Raudhatul Athfal. Data were collected through observation, documentation, and performance-based assessment, and analyzed descriptively across each cycle. The results revealed a significant improvement in children’s eye–hand coordination from the initial condition to the end of the second cycle. The use of clamp media proved effective in stimulating visual–motor coordination, as it required children to perform precise gripping, transferring, and controlled hand movements in response to visual stimuli. Furthermore, children demonstrated increased focus and better integration between visual perception and motor control. In conclusion, the implementation of sensorimotor play using clamp media is an effective and practical strategy for enhancing eye–hand coordination and supporting fine motor development in early childhood. It is recommended that educators incorporate similar interactive and manipulative media to create more engaging and developmentally appropriate learning experiences.